Increase in the antioxidant content in biscuits by infusions or Prosopis chilensis pod flour - Conforti, Paula Andrea (2021)
Nowadays there is an increasing demand for healthy biscuits. The reduction in sugar and fat level, as well as the addition of bioactive compounds, is positively associated with a healthy diet. In the present work, low-fat and low-sugar biscuits were prepared with infusions (mate, coffee, and tea) or with Prosopis chilensis pod flour (PPF). Biscuits were made with maize starch and wheat flour (gluten formulations) or with gluten-free ingredients (gluten-free). The colour, texture, and the antioxidant capacity were evaluated in dough and biscuits. Among the formulations prepared with infusions, the mate dough showed the lowest firmness (1.1 N (gluten)-24.3 N (gluten-free)). However, no significant differences were found in the fracture stress of the final products (P > 0.05). Mate gluten biscuits and PPF gluten-free biscuits showed the highest fracture strain (16.2 and 9.4%, respectively) and the lowest Young’s modulus (7.3 and 13.3 MPa, respectively) in their groups. The highest antioxidant activity was found in biscuits with mate (8.7 µmol FeSO₄/g (gluten)-4.3 µmol FeSO₄/g (gluten-free)). These values were three times higher than the ones found in the control biscuits (2.9 µmol FeSO₄/g (gluten)-3.9 µmol FeSO₄/g (gluten-free)). The present results showed that the antioxidant content in biscuits could be successfully increased with infusion addition.